2005
DOI: 10.1080/13880200590919483
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Activity of the Aqueous Leaf Extract ofIxora coccinea.

Abstract: The aim of this study was to investigate the antiinflammatory potential of an aqueous leaf extract (ALE) of Ixora coccinea (Rubiaceae) in rats after oral administration (500, 1000 and 1500 mg=kg). This was done using the carrageenan-induced paw edema (acute inflammatory model) and cotton pellet granuloma tests (chronic inflammatory model). In the former test, ALE significantly impaired both early and late phases of the inflammatory response and also the edema maintained between the two phases. In the latter te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 17 publications
3
25
1
Order By: Relevance
“…Different parts of the plant are used in traditional medicine for the treatment of a variety of infections, hypertension, menstrual irregularities, sprains, chronic ulcers and skin diseases (Batugal, 2004;Saha et al, 2008 and references cited therein Latha et al, 1995;Nayak et al, 1999). The extracts of the flowers and leaves of I. coccinea have been reported to show cytotoxic, antitumour Panikkar, 1998, 1999) and antimicrobial (Annapurna et al, 2003;Latha et al, 1995), anti-inflammatory, (Ratnasooriya et al, 2005) and antioxidant activities (Saha et al, 2008). Ursolic acid, cycloartenol esters, lupeol, oleanolic acid and sitosterol have been reported from I. coccinea leaves (Ragasa et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Different parts of the plant are used in traditional medicine for the treatment of a variety of infections, hypertension, menstrual irregularities, sprains, chronic ulcers and skin diseases (Batugal, 2004;Saha et al, 2008 and references cited therein Latha et al, 1995;Nayak et al, 1999). The extracts of the flowers and leaves of I. coccinea have been reported to show cytotoxic, antitumour Panikkar, 1998, 1999) and antimicrobial (Annapurna et al, 2003;Latha et al, 1995), anti-inflammatory, (Ratnasooriya et al, 2005) and antioxidant activities (Saha et al, 2008). Ursolic acid, cycloartenol esters, lupeol, oleanolic acid and sitosterol have been reported from I. coccinea leaves (Ragasa et al, 2004).…”
Section: Introductionmentioning
confidence: 96%
“…A previous study by Annapurna et al (2003) revealed that the leaves of I. coccinea exhibited antimicrobial activity which was comparable to streptomycin, a standard antibiotic. It was also found that the aqueous extract of I. coccinea showed antinociceptive and anti-inflammatory effects in mice (Ratnasooriya et al, 2005a(Ratnasooriya et al, , 2005b. Studies on the antioxidant activity of I. coccinea are scarce except for a recent work which showed high antioxidant properties of the flower extract.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter test, it has significantly suppressed granuloma formation (only highest dose tested). Collectively, the results has shown a promising anti-inflammatory activity against both acute and chronic inflammation (Ratnasooriya et al, 2005). The anti-inflammatory activity of methanolic leaf extract (MLE) of I. coccinea Linn.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%